Pegada Ecológica: uma ferramenta utilizada como indicador e conscientizador do consumo, aplicado na UNG Universidade, Guarulhos/SP - Regina de Oliveira Moraes Arruda; Fernanda Dall'Ara Azevedo; Fabricio Bau Dalmas (Revista Principia, 2017)
Among the functions of a university there are Teaching, Research and Extension. In order to collaborate in the extension of actions within the week of Conscious Consumption, 2016, Master in Geoenvironmental Analysis at the UNG Universidade suggested the questionnaire on the Ecological Footprint, an instrument that was developed and widely publicized by the WWF-Brazil (World Wide Fund for Nature - Brazil). The shares were held in the three campuses in the University: Center, Dutra and Itaquaquecetuba, covering about 1,000 students. Students answered the questionnaire with 18 questions and after the addition of the points, these might be classified according to the amount of renewable natural resources to maintain their standard of living and how many planets would be needed to keep this consumption if all people on the planet I had the same level of consumption. With the result of the application of this questionnaire, we can see that the students of the UNG Universidade need, on average, 2.8 planets to maintain its consumption of life, higher than the national average which is 1.6 and very close to average the UK is 3.0. When it comes to Conscious Consumption it is important each person doing the exercise to quantify and reflect on their lifestyle. Thus, this extension activity fulfilled its objectives, since the discussion on consumption was noticeable by observing the students talking and checking how are consumerist and Consumer Awareness is not limited to “shopping” but also housing, food, waste and transportation.